Resiliensi Wanita yang Mengalami Perselingkuhan dalam Rumah Tangga di Sarirejo Lamongan - Faizatul Muniroh; Muhimmatul Hasanah (Busyro : Jurnal Dakwah dan Komunikasi Islam, 2020)
The research was conducted to find out how the description of the process of resilience and the factors that influence it where as a woman it is certainly not easy after being cheated on by her husband and divorced to be able to survive in a depressed state and even deal with adversity or trauma experienced in her life, and it is not easy to be a single parent who have a dual role in educating and earning their own living. The impact of infidelity and divorce is very influential on the personality of women, families, and children. The existence of resilience factors that vary from the condition of each individual, can the individual survive in a state of stress, trauma or misery. Researchers used descriptive qualitative research methods with data collection techniques of observation, interviews and documentation. This research was conducted in Sarirejo District, Lamongan Regency with 4 single parent subjects. The results showed that the analysis of the picture of resilience showed that the four subjects had good resilience. Because these individuals can regulate negative emotions due to betrayal effectively, so they don't drag on in these emotions, can adjust to new circumstances, are able to survive under pressure and are able to play a dual role, namely educating and earning a living. Factors that influence women to be resilient are parental support, can encourage and motivate to rise from adversity and individuals are able to survive because mothers must be role models for their children. Mothers are the first educators in the family for their children.